A new metriorhynchid crocodylomorph from the Oxford Clay Formation (Middle Jurassic) of England, with implications for the origin and diversification of Geosaurini. (21st October 2018) - Foffa, Davide; Young, Mark T.; Brusatte, Stephen L.; Graham, Mark R.; Steel, Lorna
Abstract : Metriorhynchids are an extinct group of Jurassic–Cretaceous crocodylomorphs secondarily adapted to a marine lifestyle. A new metriorhynchid crocodylomorph from the Oxford Clay Formation (Callovian, Middle Jurassic) of England is described. The specimen is a large, fragmentary skull and associated single ramus of a lower jaw uniquely preserved in a septarian concretion. The description of the specimen reveals a series of autapomorphies (apicobasal flutings on the middle labial surface of the tooth crowns, greatly enlarged basoccipital tuberosities) and a unique combination of characters that warrant the creation of a new genus and species: Ieldraan melkshamensis gen. et sp. nov. This taxon shares numerous characters with the Late Jurassic–Early Cretaceous genus Geosaurus : tooth crowns that have three apicobasal facets on their labial surface, subtly ornamented skull and lower jaws elements, and reception pits along the lateral margin of the dentary (maxillary overbite). Phylogenetic analysis places this new species as the sister taxon to Geosaurus . The new taxon adds valuable information on the time of origin of the macrophagous subclade Geosaurini, which was initially thought to have evolved and radiated during the Late Jurassic. The presence of Ieldraan melkshamensis, the phylogenetic re-evaluation of Suchodus durobrivensis as a Plesiosuchus sister taxon and recently identified Callovian Dakosaurus -like specimens in the Oxford Clay Formation, indicate that all major Geosaurini lineages originated earlier than previously supposed. This has major implications for the evolution of macropredation in the group. Specifically, we can now demonstrate that the four different forms of true ziphodonty observed in derived geosaurins independently evolved from a single non-functional microziphodont common ancestor. http://zoobank.org/urn:lsid:zoobank.org:pub:7A400670-A339-463F-8CD4-8704745CB312